The sage handbook of social media (SAGE Reference, 2019)
The world is in the midst of a social media paradigm. Once viewed as trivial and peripheral, social media platforms like Twitter, Facebook and WeChat have become an important part of the information and communication infrastructure of society. They are bound up with business and politics as well as everyday life, work, and personal relationships. This international Handbook addresses the most significant research themes, methodological approaches and debates in the study of social media. It contains substantial chapters written especially for this book by leading scholars from a range of disciplinary perspectives, covering everything from computational social science to sexual self-expressio.